The Implementation of the Right Raw Material Inventory Control System in an Effort to Improve the Results of the Production Process in UD. R&D Handicraft Lamongan - Hanif Romadhon; Abid Muhtarom; Mohammad Yaskun (Sean Institute, 2025)
A company that is established has the goal of achieving the expected profit. The achievement of the company's goals is determined by the raw materials that are processed in production, so the company needs proper control of the raw material inventory. This is very important for the company because it greatly affects the profit earned by the company. In analyzing the data, the author uses quantitative methods . The data analysis determines the control of raw material inventory by using the EOQ method to determine the optimal amount of purchase, the Safety Stock method to determine the safety inventory and the Re Order Point method to determine when the company has to reorder raw materials. The results of the calculation of the total average purchase of raw materials using the EOQ method are more efficient than the company's policy. In addition, the inventory costs incurred by the company if using the EOQ method are lower.